2013
DOI: 10.1021/ma302616a
|View full text |Cite
|
Sign up to set email alerts
|

Nanorheological Mapping of Rubbers by Atomic Force Microscopy

Abstract: A novel atomic force microscopy (AFM) method is used for nanometer-scale mapping of the frequency dependence of the storage modulus, loss modulus, and loss tangent (tan δ) in rubber specimens. Our method includes a modified AFM instrument, which has an additional piezoelectric actuator placed between the specimen and AFM scanner. The specimen and AFM cantilever are oscillated by this actuator with a frequency between 1 Hz and 20 kHz. On the basis of contact mechanics between the probe and the sample, the visco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
78
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 27 publications
5
78
0
Order By: Relevance
“…AFM tapping mode has been used for polymeric surfaces information with nanoscale resolution [9][10][11] . High-resolution surface results are obtained through this mode of analysis, since the images provide height (relief surface) and phase (combination of sample and AFM-probe characteristics) [12,13] .…”
Section: De Sousa F D B; Scuracchio C H -The Use Of Atomic Formentioning
confidence: 99%
See 1 more Smart Citation
“…AFM tapping mode has been used for polymeric surfaces information with nanoscale resolution [9][10][11] . High-resolution surface results are obtained through this mode of analysis, since the images provide height (relief surface) and phase (combination of sample and AFM-probe characteristics) [12,13] .…”
Section: De Sousa F D B; Scuracchio C H -The Use Of Atomic Formentioning
confidence: 99%
“…The authors concluded that the interacting polymer layer share the same segmental relaxation dynamics with the bulk rubber due to the presence of a flexible chain between the matrix and the nanoparticles. Igarashi et al [11] also used another novel AFM method for nanometer-scale mapping of the frequency dependence of viscoelastic properties of rubbers. It was used an additional piezoelectric actuator placed between the specimen and AFM scanner.…”
Section: De Sousa F D B; Scuracchio C H -The Use Of Atomic Formentioning
confidence: 99%
“…Igarashi et al extended the modulation frequency up to 20 kHz using a sample stage piezoelectric actuator to determine viscoelastic properties of homopolymers and rubbers. 42 One challenge in these approaches is that one must consider the influence of hydrodynamic drag on the oscillating probe by the surrounding medium. This drag can confound the measurement of the viscous properties of the sample, and thus must be accounted for when quantifying mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Thus, stepwise changes in the frequency enable an estimate of the frequency-dependent behavior of G* for single cells in a local region. [11][12][13] For more detailed understanding of spatial dependence of rheological properties in soft materials, mapping the frequency-dependent rheology of "static" polymer materials 14,15 and living cells 16 can be performed by sweeping the frequency during single-frequency force modulation AFM.…”
mentioning
confidence: 99%